Hyperbranched block copolymer from AB2 macromonomer: Synthesis and its reaction‐induced microphase separation in epoxy thermosets. Issue 3 (6th August 2015) - Li, Jingang; Xiang, Yixin; Zheng, Sixun
ABSTRACT: In this contribution, we reported the synthesis of a hyperbranched block copolymer composed of poly(ε‐caprolactone) (PCL) and polystyrene (PS) subchains. Toward this end, we first synthesized an α‐alkynyl‐ and ω, ω′‐diazido‐terminated PCL‐ b ‐(PS)2 macromonomer via the combination of ring‐opening polymerization and atom transfer radical polymerization. By the use of this AB2 macromonomer, the hyperbranched block copolymer ( h ‐[PCL‐ b ‐(PS)2 ]) was synthesized via a copper‐catalyzed Huisgen 1, 3‐dipolar cycloaddition (i.e., click reaction) polymerization. The hyperbranched block copolymer was characterized by means of 1 H nuclear magnetic resonance spectroscopy and gel permeation chromatography. Both differential scanning calorimetry and atomic force microscopy showed that the hyperbranched block copolymer was microphase‐separated in bulk. While this hyperbranched block copolymer was incorporated into epoxy, the nanostructured thermosets were successfully obtained; the formation of the nanophases in epoxy followed reaction‐induced microphase separation mechanism as evidenced by atomic force microscopy, small angle X‐ray scattering, and dynamic mechanical thermal analysis. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 368–380 Abstract : The synthesis of a hyperbranched block copolymer composed of poly(ε‐caprolactone) (PCL) and polystyrene (PS) subchains via a copper‐catalyzed Huisgen 1, 3‐dipolar cycloaddition polymerization is reported.